Initial experiences of an english-speaking digital assistant for tobacco cessation in India - Enub Ali; Nitin Antony; Ankur Sachdeva; Smita N. Deshpande (Industrial Psychiatry Journal)
Background: The WHO tobacco control team established the Access Initiative for Quitting Tobacco (AIQT) in July 2020. The AIQT team developed a virtual assistant “Florence” to provide digital counseling services to people willing to quit tobacco. Aim: To assess tobacco users’ experience of using WHO digital health assistant “Florence” and to track their behavior changes. Materials and Methods: The study was conducted at a tertiary care Teaching Hospital in Delhi-NCR, India from November 2021 to March 2022. A total of 102 English-speaking tobacco users were enrolled through snowballing and online requests to use Florence (https://www.who.int/campaigns/Florence), once at baseline, and pursue as often as they wish during the next three months. A predesigned WHO questionnaire (Florence Introductory Questionnaire and Florence User Follow-up Questionnaire) was used to assess participants’ experiences of using Florence and track changes in tobacco use behavior at follow-up. Statistical analysis was performed through SPSS-22 using appropriate frequency distribution parameters and nonparametric tests to assess acceptance and efficacy of Florence. Results: Most participants at baseline, over 3-5 minutes, felt that Florence could not understand their speech (48%), and needed improvement in advice and information on quitting and tobacco use (52%) but felt comfortable interacting with Florence (42.2%). However, participants who re-visited Florence during the next 3 months (12/102) agreed that Florence helped them make a quit plan and used the recommended toll-free quit (9/12). Overall, there was a significant increase in proportion of participants who did not consume tobacco in the last 07 days after using Florence (09 versus 25 of 102, P < 0.01) and made quit plans (07 versus 15 of 102, P < 0.01) compared to baseline. Conclusion: Considering the ease, accessibility, and amount of time spent with this virtual assistant, Florence appears a positive step forward in tobacco cessation.